Moderating Effect of IFRS Compliance on the Relationship between Ownership Structure and Financial Reporting Quality - Ilugbo, Anne Nwayinbunwa; Josiah, Mary; Ozele , Clement Edojor (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study investigates the moderating effect of International Financial Reporting Standards (IFRS) on the relationship between corporate governance, specifically ownership structure, and financial reporting quality in listed non-finance firms in Nigeria. Utilizing an ex-post facto research design, the study drew its data from 67 non-finance firms listed on the Nigerian Exchange Group over a ten-year period (2012-2021). The study employs purposive sampling and hierarchical regression analysis to explore the complex connection between IFRS adoption and ownership structures, revealing that IFRS plays a significant role in enhancing the quality of financial reporting. The findings indicate that while ownership concentration may weaken financial reporting quality in the absence of IFRS, the adoption of IFRS significantly moderates this effect, leading to improved transparency and reduced earnings manipulation. This study contributes to the existing literature by providing empirical evidence from a less developed market context, emphasizing the critical interaction between global accounting standards and corporate governance mechanisms. The study concludes that robust enforcement of IFRS compliance, combined with targeted capacity building for financial professionals, is essential to ensure high-quality financial reporting in Nigeria. Key implications include the need for enhanced regulatory oversight and collaboration between regulatory bodies and professional accounting organizations to foster consistent adherence to IFRS, thereby improving the reliability of financial statements and boosting investor confidence.